Preparing the Dietetic Workforce of the Future – Developing Innovative Placements in Social Care Settings - Mackenzie, Myra; Newman, Evelyn (International Journal of Practice-based Learning in Health and Social Care, 2017)
Practice placements are key to the training of an allied health professional, supporting the integration of theoretical and practical knowledge, allowing the development of key skills and enculturation to a professional role. Practice placements in dietetic pre-registration training have largely focussed on clinical/health care settings, with the students based in dietetic departments. Current developments in integrated health and social care provision in the United Kingdom mean there is a compelling need to develop a workforce equipped to work across sectors to effectively support people’s nutritional needs. Against this background, a partnership group of healthcare and managerial professionals, representing NHS Education for Scotland (NES), NHS Highland (NHSH), a private care home group based in the North of Scotland and Robert Gordon University worked together to pilot and develop a model for the placement of student dietitians within social care settings (initially care homes). This novel approach embeds students in a social care setting for part of their placement rather than having them based within a dietetic department. The placements were positively evaluated and widely shared via Allied Health Profession (AHP) blogposts and in publications such as the Care Inspectorate newsletter, and other Scottish Health Boards are now developing local models of dietetic social care placements. There is a recognition that practice placement models should prepare the dietitians of the future for working beyond NHS environments, and that alternative models of placement should be explored from the perspective of raising the profile of the profession and ensuring sustainability of placement provision.